For Better or for Worse: A Look Into Neutrophils in Traumatic Spinal Cord Injury - Zivkovic, Sandra; Ayazi, Maryam; Hammel, Grace; Ren, Yi (Frontiers in Cellular Neuroscience, 2021)
Neutrophils are short-lived cells of the innate immune system and the first line of defense at the site of an infection and tissue injury. Pattern recognition receptors on neutrophils recognize pathogen-associated molecular patterns or danger-associated molecular patterns, which recruit them to the destined site. Neutrophils are professional phagocytes with efficient granular constituents that aid in the neutralization of pathogens. In addition to phagocytosis and degranulation, neutrophils are proficient in creating neutrophil extracellular traps (NETs) that immobilize pathogens to prevent their spread. Because of the cytotoxicity of the associated granular proteins within NETs, the microbes can be directly killed once immobilized by the NETs. The role of neutrophils in infection is well studied; however, there is less emphasis placed on the role of neutrophils in tissue injury, such as traumatic spinal cord injury. Upon the initial mechanical injury, the innate immune system is activated in response to the molecules produced by the resident cells of the injured spinal cord initiating the inflammatory cascade. This review provides an overview of the essential role of neutrophils and explores the contribution of neutrophils to the pathologic changes in the injured spinal cord.